Tyrosylprotein sulfotransferase suppresses ABA signaling via sulfation of SnRK2.2/2.3/2.6 - Wang, Jun; Wang, Chunyan; Wang, Tianrun; Zhang, Shizhong; Yan, Kang; Yang, Guodong; Wu, Changai; Zheng, Chengchao; Huang, Jinguang (Journal of integrative plant biology, 2023)
SUMMARY Phytohormone abscisic acid (ABA) plays vital roles in stress tolerance, while long‐term overactivation of ABA signaling suppresses plant growth and development. However, the braking mechanism of ABA responses is not clear. Protein tyrosine sulfation catalyzed by tyrosylprotein sulfotransferase (TPST) is a critical post‐translational modification. Through genetic screening, we identified a tpst mutant in Arabidopsis that was hypersensitive to ABA. In‐depth analysis revealed that TPST could interact with and sulfate SnRK2.2/2.3/2.6, which accelerated their degradation and weakened the ABA signaling. Taken together, these findings uncovered a novel mechanism of desensitizing ABA responses via protein sulfation. Tyrosylprotein sulfotransferase alleviates the side effects of abscisic acid responses by sulfating the kinases SnRK2.2, SnRK2.3, and SnRK2.6, and accelerating their degradation.